28.9k views
3 votes
What is the exact value for the expression the square root of 56. − the square root of 14. + the square root of 126.? Simplify if possible. the square root of 14. 4 the square root of 14. 2 the square root of 42. 8 the square root of 42.

User TreeWater
by
5.3k points

2 Answers

1 vote


\bf √(56)-√(14)+√(126)~~ \begin{cases} 56=&2\cdot 2\cdot 2\cdot 7\\ &2^2\cdot 14\\ 126=&2\cdot 3\cdot 3\cdot 7\\ &2\cdot 3^2\cdot 7\\ &3^2\cdot 14 \end{cases}\implies √(2^2\cdot 14)-√(14)+√(3^2\cdot 14) \\\\\\ \stackrel{\textit{let's add the like-terms}}{2√(14)-√(14)+3√(14)}\implies 4√(14)

User Jim McCurdy
by
5.1k points
5 votes

Answer:

Explanation:

sqrt(56) = sqrt(4*14) = 2*sqrt(14)

sqrt(126)= sqrt(9*14) = 3*sqrt(14)

2*sqrt(14) - sqrt(14) + 3*sqrt(14)

5sqrt(14) - sqrt(14)

4*sqrt(14)

====================

The second one is not clear enough.

User Rottitime
by
5.7k points